393 DECONVOLUTING THE COMPLEXITY OF LONG NON-CODING RNAS AND ESOPHAGEAL CARCINOMA FOR POTENTIAL CLINICAL IMPLICATIONS. (17th September 2021) - Luan, Siyuan; Yang, Yushang; Zhang, Shouyue; Zeng, Xiaoxi; Xiao, Xin; Fu, Leilei; Liu, Bo; Yuan, Yong
Abstract: : Long non-coding RNAs (lncRNAs), a type of transcriptional products with more than 200 nucleotides in length, have been less characterized compared to protein-coding RNAs so far. However, it is increasingly evident that lncRNAs are key players involved in multiple genetic and epigenetic activities during the carcinogenesis of neoplastic diseases. Currently, accumulating data have pointed out the close connection between lncRNAs and esophageal carcinoma (EC), shedding light on further unravelling the complexity of lncRNAs and EC. Methods: In this review, we thoroughly collect the evidence regarding original studies on EC-related lncRNAs by searching in MEDLINE/PubMed, Embase and WOS/SCI. We especially focus on summarizing EC-related lncRNAs based upon more updated evidence, and further discuss their different features from various perspectives, including regulatory mechanisms, functional roles in cancer hallmarks, as well as potential diagnostic and therapeutic applications, which would together reveal the complexity of lncRNAs and EC for potential clinical applications. Results: We discuss over thirty EC-related lncRNAs in total, most of which function as oncogenes that promote cancer development, while the others function as tumor suppressors. Regulatory mechanisms included sponging miRNAs, direct interaction with proteins, and exosome visicle-based intercellular communication. Based upon these modes of actions, lncRNAs play multiple roles in cancer hallmarks such as uncontrolled cell growth, evasion of programmed cell death, invasion and metastasis. Moreover, lncRNAs packaged in exosomes have unique potency to serve as diagnostic biomarkers; some lncRNAs show great potential to predict patients' chemical resistance and may be crucial targets to improve chemoradiotherapy and targeted therapy. Conclusion: Over the past few years, the research of EC-related lncRNAs maintain obviously rapid development, yet further exploration of exact mechanisms and clinical applications that lncRNAs can offer need to be done. Indeed, LncRNAs hold the promise of being applied in multiple clinical scenarios, especially early diagnosis of EC, improvement of sensitivity to chemotherapy/radiotherapy, and development of small-molecule targeted drugs.